Analgesic effects of the cathepsin K inhibitor L-006235 in the monosodium iodoacetate model of osteoarthritis pain. (November 2018) - Nwosu, Lilian N.; Gowler, Peter R.W.; Burston, James J.; Rizoska, Biljana; Tunblad, Karin; Lindström, Erik; Grabowska, Urszula; Li, Li; McWilliams, Dan F.; Walsh, David A.; Chapman, Victoria
Abstract: Introduction: The mounting evidence that osteoclasts play an important role in osteoarthritis (OA) pain lead us to investigate the effects of L-006235, a potent and selective inhibitor of cathepsin K, on pain behaviour and joint pathology in a model of OA pain. Methods: Effects of preventative (30 and 100 mg/kg) and therapeutic (100 mg/kg) oral dosing with L-006235 on weight-bearing asymmetry, hind paw withdrawal thresholds, cartilage and bone pathology, synovial inflammation, and drug exposure were studied in the monosodium iodoacetate rat model of OA pain. Results: Preventative L-006235 inhibited weight-bearing asymmetry from day 14, with this measure nearly abolished by the higher dose. In the same treatment setting, L-006235 prevented lowering of hind paw withdrawal thresholds from day 7. Exposure to L-006235 in plasma was higher for the 100 mg/kg dose, compared with 30 mg/kg. Therapeutic dosing with L-006235 from day 14 significantly inhibited weight-bearing asymmetry, compared with monosodium iodoacetate vehicle rats. Regression analysis revealed a significant interaction coefficient of the effects of L-006235 on weight-bearing asymmetry and synovitis score, but not for cartilage damage nor osteophyte scores. Conclusion: Our novel finding that cathepsin K inhibition is analgesic in a clinically relevant model of OA pain provides new evidence for the therapeutic potential of this target. Abstract : Supplemental Digital Content is Available in the Text.